Pengelolaan Hara pada Varietas Padi Toleran Rendaman - Ikhwani, Ikhwani; Makarim, A. Karim (Jurnal Penelitian Pertanian Tanaman Pangan, 2011)
Nutrient management, by combining rice varieties tolerant to water submergence with plant spacing and timing and mode of fertilizer application is expected to reduce rice yield loss due to submergence in the flood-prone wetland. A study on nutrient management (fertilization) was conducted aiming to determine the effect of submergence on growth and production of rice varieties tolerant to submergence. The experiment was conducted on a special pond to simulate wetland conditions prone to submergence at the Sukamandi Experimental Station, Indonesia Center of Rice Research using a randomized bock design with factorial 2 x 5 three replications. The treatments consisted of two rice varieties, namely: (1) prill urea, (2) prill urea + briquette urea, (3) briquette urea, (4) prill urea + silicate and (5) urea in mudball. The fertilizer was given at 0 days after transplanting (DAT), 7 DAT, 30 DAT, and 42 DAT. The same treatments were made in a different ponds as a control but without submergence. Submergence was applied from 14 to 24 DAP (10 days). Results of the experiment showed that of 400 hills that were planted (16 m2/plot), after immersion for 10 days, the number of IR64 that survived ranged from 7-44 hills/plot, for IR64, whereas for IR64 sub-1 the survival plant hills are between 182 and 216. It indicated there are still many hills damaged by submergence for 10 days even for the tolerance rice variety. At harvest, the relative yields for submerged treatments compared with for non submergence ones are as follows 58.5%; 75.2%; 119.6%; 87.7%; and 77.7% namely for the respective fertilizer treatments; (1) 30 PR + 40 PR + 50 PR; (2) 60 BR + 30 PR + 30 PR; (3) 60 BR + 60 BR + 0; (4) No 1 + silicate and (5) 40 MB + 80MB + 0. Through this research we found the best N application using a briquette urea 9.34 ton dry (14% mc) grain.